Adult-Onset Neuronal Ceroid Lipofuscinosis With a Novel DNAJC5 Mutation Exhibits Aberrant Protein Palmitoylation - Huang, Qiang; Zhang, Yong-Fang; Li, Lin-Jie; Dammer, Eric B.; Hu, Yong-Bo; Xie, Xin-Yi; Tang, Ran; Li, Jian-Ping; Wang, Jin-Tao; Che, Xiang-Qian; Wang, Gang; Ren, Ru-Jing (Frontiers in Aging Neuroscience, 2022)
Neuronal ceroid lipofuscinosis (NCL) is composed of a group of inherited neurodegenerative diseases, with the hallmark of lipofuscin deposit (a mixture of lipids and proteins with metal materials) inside the lysosomal lumen, which typically emits auto-fluorescence. Adult-onset NCL (ANCL) has been reported to be associated with a mutation in the DNAJC5 gene, including L115R, L116Δ, and the recently identified C124_C133dup mutation. In this study, we reported a novel C128Y mutation in a young Chinese female with ANCL, and this novel mutation caused abnormal palmitoylation and triggered lipofuscin deposits.